Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

“Waffle” pools in ditched salt marshes: assessment, potential causes, and management - Joseph A. M. Smith; Susan C. Adamowicz; Geoffrey M. Wilson; Ilia Rochlin (Wetlands Ecology and Management, 2022)

Coastal Impacts, Recovery, and Resilience Post-Hurricane Sandy in the Northeastern US - Amanda L. Babson; Richard O. Bennett; Susan Adamowicz; Sara Stevens (Estuaries and Coasts, 2020)
Post-Hurricane Sandy research has improved our understanding of coastal resilience during major storm events, accelerated sea level rise, and other climate-related factors, helping to enhance science-based decision-making, restoration, and management of coastal systems. The central question this special section examines is: “looking across the breadth of research, natural resource management actions and restoration projects post-Hurricane Sandy, what can we say about coastal impact, recovery, and resilience to prepare for increasing impacts of future storms?” These five studies, along with lessons from other published and unpublished research, advance our understanding beyond just the documentation of hurricane impacts but also highlights both natural and managed recovery, thereby advancing the developing field of coastal resilience.

Hurricane Sandy Effects on Coastal Marsh Elevation Change - Alice G. Yeates; James B. Grace; Jennifer H. Olker; Glenn R. Guntenspergen; Donald R. Cahoon; Susan Adamowicz; Shimon C. Anisfeld; Nels Barrett; Alice Benzecry; Linda Blum; Robert R. Christian; Joseph Grzyb; et al. (Estuaries and Coasts, 2020)

Mitigating the Legacy Effects of Ditching in a New England Salt Marsh - David M. Burdick; Gregg E. Moore; Susan C. Adamowicz; Geoffrey M. Wilson; Chris R. Peter (Estuaries and Coasts, 2020)

Elevation change and the vulnerability of Rhode Island (USA) salt marshes to sea-level rise - Kenneth B. Raposa; Marci L. Cole Ekberg; David M. Burdick; Nicholas T. Ernst; Susan C. Adamowicz (Regional Environmental Change, 2017)

Erratum to: Influence of Physical Manipulations on Short-Term Salt Marsh Morphodynamics: Examples from the North and Mid-Atlantic Coast, USA - Tracy Elsey-Quirk; Susan C. Adamowicz (Estuaries and Coasts, 2016)

Influence of Physical Manipulations on Short-Term Salt Marsh Morphodynamics: Examples from the North and Mid-Atlantic Coast, USA - Tracy Elsey-Quirk; Susan C. Adamowicz (Estuaries and Coasts, 2016)

Carbon Sequestration in Tidal Salt Marshes of the Northeast United States - Katherine Drake; Holly Halifax; Susan C. Adamowicz; Christopher Craft (Environmental Management, 2015)

Use of Structured Decision Making to Identify Monitoring Variables and Management Priorities for Salt Marsh Ecosystems - Hilary A. Neckles; James E. Lyons; Glenn R. Guntenspergen; W. Gregory Shriver; Susan C. Adamowicz (Estuaries and Coasts, 2015)

Integrated Marsh Management (IMM): a new perspective on mosquito control and best management practices for salt marsh restoration - Ilia Rochlin; Mary-Jane James-Pirri; Susan C. Adamowicz; Roger J. Wolfe; Paul Capotosto; Mary E. Dempsey; Thomas Iwanejko; Dominick V. Ninivaggi (Wetlands Ecology and Management, 2012)

The Effects of Integrated Marsh Management (IMM) on Salt Marsh Vegetation, Nekton, and Birds - Ilia Rochlin; Mary-Jane James-Pirri; Susan C. Adamowicz; Mary E. Dempsey; Thomas Iwanejko; Dominick V. Ninivaggi (Estuaries and Coasts, 2012)

New England salt marsh pools: A quantitative analysis of geomorphic and geographic features - Susan C. Adamowicz; Charles T. Roman (Wetlands, 2005)